DIVERSIFICATION IN UTILISATION OF OF TRASH FISH BY GAMMA IRRADIATION. - GHADI, S v; MADHAVAN, V N; KUMTA, U S (Fishery Technology, 2017)
Radiation pasteurisation enhances the shelf stability of trash fish varieties and enables the grading of fish depending upon the freshness quality. As against the ice-chilled fish which spoils within 8-10 days, exposure to 100 Krad and storage at ice temperature helps in maintaining the quality in Grade I, II or III up to 10, 20 or 25 days respectively. The improvement in. quality. thus provides scope fer greater utilisation of trash fish for variou3 secondary products.